Genome‐wide association studies for rice seed germination under drought stress using 3VmrMLM - Bin Yang; Shaona Chen; Zhao Zheng; Jiali Zeng; Jiping Liu; Hua Zhao; Yixiong Zheng (Food and Energy Security, 2024)
Abstract Improving seed germination under drought stress has the potential to increase crop yield in dry direct‐seeded rice. In this study, a genome‐wide association study (GWAS) was conducted to determine the genetic basis of seed germination under drought stress in a panel of 165 rice accessions using a multi‐locus compressed variance‐component mixed model, 3VmrMLM. A total of 33 quantitative trait nucleotides (QTNs) were identified in association with drought tolerance during seed germination. Around these QTNs, eight were found to be co‐localized with known drought‐related genes. Furthermore, a causal candidate gene, OsGA2ox5, which encodes a gibberellin (GA) 2‐oxidase, was identified for QTN‐Chr07_242906 by integrating linkage disequilibrium (LD) analysis and gene expression analysis. Knockout mutation of OsGA2ox5 resulted in delayed seed germination and retarded seedling growth under drought stress. RNA‐seq analysis revealed that OsGA2ox5 regulates drought tolerance during seed germination mainly by modulating carbohydrate metabolism. Additionally, a non‐synonymous coding variant in OsGA2ox5, SNP‐Chr07_218893, was found to be strongly associated with drought tolerance level during seed germination. These findings provide valuable information for further exploration of novel drought‐related genes and genetic improvement of rice drought tolerance in the future.